Designing a research to study the status of political science in Arab universities - شمش, د. علی محمد (Dirasat in Economics and Business, 1979)
Scientific research in political science does not differ in its style and procedural steps from scientific research in any science, because research in political science begins with an initial and basic step, which is to identify the problem and then proceed from it to the rest.